(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Prameha is a disease with different pathological conditions as per Ayurveda, comparable to Type 2 Diabetes mellitus. The main line of therapeutic intervention for Prameha, a disease due to over-nourishment, is Apatarpana (depleting regimens of Ayurveda to reduce the bulk of body tissues, particularly Meda and Mamsa dhatu in the present context). As a general principle of Ayurveda diagnosis, a disease is dynamic and changes its status and presentation with time, diet, and interventions. Complementing this, each therapeutic intervention is defined with deficit, optimum, and excess use features. Administering the intervention less than or beyond the requirement may harm the individual, resulting in hampered structure and/or function of other body components. In the present review, we have attempted to put forth this principle of need-based Apatarpana and Santarpana (bulk/strength promoting therapies of Ayurveda) interventions, in managing Prameha with special reference to Type 2 Diabetes Mellitus.